On the Mineralogy and Paragenesis of Tugtupite Na8Al2Be2Si8O24(Cl, S)2. - Sørensen, H. M.; Petersen, Ole V. (Meddelelser om Grønland, 1971)
Tugtupite, Na8Al2Be2Si8O24(Cl, S)2 is colourless to red, tetragonal, pseudocubic and forms triplet twins on 101. c: a = 1.0269 ± 0.0003, d = 2.33 g/cm3. nε = 1.499 ± 0.001, nω = 1.495 ± 0.001. a0 = 8.637 - 8.643, c0 = 8.867 - 8.870, V0 = 662 Å3. The description of the crystal structure is taken from DANØ (1966) . The mineral occurs in hydrothermal veins in the Ilímaussaq alkaline intrusion, South Greenland, and in the Lovozero alkaline intrusion, Kola Peninsula (beryllosodalite). A number of occurrences of tugtupite in Ilimaussaq are described. Tugtupite is most commonly associated with albite, analcime and Li-mica and is generally secondary after chkalovite. The paragenesis and origin of the mineral and a number of asssociated beryllium silicates are discussed.